EFEKTIFITAS PENGGUNAAN PROBIOTIK PADAPENTOKOLAN UDANG VANAME (Litopenaeus vannamei) - Andi Tamsil; Hasnidar Hasnidar (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2025)
Vannamei shrimp (Litopenaeus vannamei) requires feed management and health to support growth and survival. One of the widely used approaches is the addition of probiotics in feed. This study aims to evaluate the effect of probiotic supplementation at different doses through feed on the survival and growth of vannamei shrimp during the nursery stage. The study was conducted experimentally using four treatments: A (no probiotic/control), B (2 ml/kg feed), C (3 ml/kg feed), and D (4 ml/kg feed), each with three replications. Shrimp were stocked at a density of 100 individuals per liter and reared in a controlled system. Observed parameters included survival rate (%), absolute weight gain (g), specific growth rate (SGR, %/day), and water quality. The results showed that probiotic supplementation influenced the survival and growth performance of vannamei shrimp, although the differences were not statistically significant (p > 0.05). Treatment B (2 ml/kg feed) yielded the highest results, with a survival rate of 61.3%, an average absolute weight gain of 8.8 g, and the highest specific growth rate compared to other treatments. Treatment A (without probiotics) showed the lowest performance in both survival and growth. Water quality parameters (temperature, pH, DO, and ammonia) were within the optimal range for vannamei shrimp growth.